Re-thinking Incarnation: An Asian Woman's Perpective - Orevillo-Montenegro, Muriel (Silliman Journal, 2023)
Incarnation is the Christian doctrine that articulates the belief that God became flesh in Jesus of Nazareth, the Christ. This paper argues that the doctrine needs rethinking not only because it has provided a romanticized justification for the violence of the cross, but because it conveys androcentric concepts that privilege the men and marginalize women and discriminate the female body and sexuality by associating it with sin. Consequently, it removes Mary from her femaleness and humanity and makes maleness ontologically necessary for incarnation. Moreover, the traditional doctrine of incarnation is exciusivist and privileges the story of only one people. Yet, God is incarnate in many forms and ways. In dismantling the grand narratives of Christianity that have fixed God's revelation in Jesus, Asian feminist theologians have argued that while Jesus is recognized as the epiphany of God, He may not be the sole embodiment of God's revelation. incarnation is not even limited to a human figure. Women also experience God as Christ embodied in other ecological forms. Therefore, believers need to understand that incarnation is the continuous flow of the relationship between God and human beings, and other created beings on Earth.